Nggana Ro Nggoa Tradition: Symbolic Meaning and Social Function of Birth Ceremony in Mbojo Muslim Community - Nurfah Nurfah (CV. Intake Pustaka, 2025)
The Nggana ro Nggoa tradition is part of the local wisdom of the Mbojo Muslim community in Wora Village related to the cycle of life, especially the birth of children. This research aims to: First, to describe the procession of the Nggana ro Nggoa ceremony tradition in the Mbojo Muslim community. Second, to reveal the symbolic meaning contained in each stage of the ceremony. Third, analyze the social, cultural, and religious functions of the tradition in people's lives. This research uses a descriptive qualitative approach. Data collection techniques included participatory observation, in-depth interviews with traditional leaders, parents, and religious leaders, and documentation of the ceremony procession. Data were analyzed thematically through the stages of data reduction, data presentation, and conclusion drawing. Data validity was strengthened with source and method triangulation techniques. Based on the results of the research, it was found that this ceremony includes a series of stages, such as Kiri Loko, Cafi Sari, Baka Sari, Boru Honggo, Aqiqah, and Dore. Each stage has symbols and values: yellow rice (wura bongi monca) symbolizes hope for blessings, one cent as an economic reminder, eggs and coconut oil as a symbol of safety, as well as prayers and Islamic naming as a form of integration of religious values. The symbols in the ceremony contain religious, social, and moral meanings, such as hope for the safety, welfare, and future of the child. This tradition also functions as a medium for value education, preservation of cultural identity, strengthening social solidarity, and a means of religious expression for the community. Thus, Nggana ro Nggoa is not only a traditional ritual, but also a reflection of the harmony between Islamic values and local culture.